Analisis Pengungkapan Laporan Keuangan Pemerintah Daerah Ditinjau dari Akun Persediaan di Sumatera - Putri Intan Permata Sari; Suhairi Suhairi; Nini Syofriyeni (Universitas Batanghari Jambi, 2021)
This study attemps to analyze disclosure of inventories account in local government financial statement (LGFS) regencies and cities in Sumatera in the year 2017 on the disclosure in PP 71/2010 Government Accounting Standards Number 5, as well as perceive the difference disclosure of a build up in inventories account on LGFS that obtains unqualified opinion, qualified opinion, disclaimer opinion, and knowing how the perception of BPK toward the disclosure of an inventories account. The data used in this research as many as 154 regencies and the cities that has been audited by BPK. Secondary data was used in the study in the form of audit report LGFS and PP 71/2010 as well as the primary data in an interview to the auditor team in BPK that it is processed using a method of content analysis. The research results show that BPK perception of inventory account disclosure is that there are still problems in inventory disclosure carried out by regional governments with different cases. In addition, there were 24 LGFS that had significant inventory value on their total assets including 22 LGFS obtained unqualified opinion and 2 LGFS obtained qualified opinion with an average inventory disclosure of 54.17%, but still get records by examiner regarding administration of inadequate inventories. The disclosure of inventories account in LGFS regencies and cities in Sumatera years 2017 has been good enough with an average of 55,38% with the highest percentage of disclosure in 100,00% and the lowest is 14,29%. In addition, there is no difference in the disclosure of inventories account on LGFS that obtained unqualified opinion and besides unqualified opinion.